One Year Audit of Post Tonsillectomy Haemorrhage at Limerick University Hospital, Ireland - Matin, Abdul; Attique, Sarwar; Hossain, Tanvir; Hughes, Joseph; Prazenica, Pavol; Almanassra, Alaa; Ryan, Stephen; Taous, Ahmmad (Bangladesh Journal of Otorhinolaryngology, 2024)
Objectives: To assess post tonsillectomy haemorrhage and rate of readmission , their outcomes for patients operated by different consultant surgeons ,using different methods, patients age, use of antibiotics during the period of one year and any relation with post tonsillectomy haemorrhage to these variables. Study design; A retrospective audit of all tonsillectomies done in one year period by different consultants using different methods. Out comes were measured for post tonsillectomy bleeding using the Flinders modification of Stammberger criteria. Method: This was a retrospective study and data was collected from theatre log book Limerick University Hospital, Ireland. Total number of patient was 210. Tonsillectomy was done by different surgeons with different methods. Computer database Hype and daily ward round record sheets kept by the NCHD were utilized to collect number of patients admitted with post tonsillectomy haemorrhage. Results: Out of 210 tonsillectomies done, 24 patients (11.4%) readmitted with post tonsillectomy bleeding and 7 patients (3.3%) returned to theatre. Haemorrhage is more observed in age group 12 or above than age group below 12 (26.4% vs 3.6%) and bipolar diathermy than coblation (25.0% vs 9.4%). There is no statistically significant diffences in length of stay or use of antibiotic related to secondary haemorrhage. 58.3% of the readmitted patients were treated conservatively. Conclusion: By using Flinders modification of Stammberger criteria, it gives types of haemorrhage and their severity. Prospective audit with introduction of new surgical proforma will allow ease of continual re audit of potential aetiological factors, operative outcomes and adverse events. Bangladesh J Otorhinolaryngol 2023; 29(2): 67-73